Development of an Initial Risk Identification and Risk Validation Framework to Support Sustainable Geo-Ecotourism Infrastructure in Osing Kemiren Village - Fikca Ayuk Safitri; Yuni Ulfiyati; Enes Ariyanto Sandi (STMIK Widya Cipta Dharma, 2026)
This study aims to identify, validate, and develop risk mitigation strategies for geo eco tourism infrastructure in Osing Kemiren Tourism Village, Banyuwangi Regency. The research methods include risk identification through field observations and recent literature review, risk classification based on environmental, socio-cultural, and operational categories, and risk validation through focused group discussions (FGDs) involving local communities and stakeholders. The results indicate that the main risks involve environmental degradation, socio-cultural changes, and operational constraints in tourism infrastructure. Based on the validation process, high-priority risks are addressed through mitigation strategies, including waste management, preservation of Osing cultural heritage, maintenance of tourist pathways, and active community participation in site management. The implementation of these strategies is expected to support the development of safe, environmentally friendly, and sustainable infrastructure, while enhancing local community engagement. This study provides a scientific basis for tourism managers and policymakers to design sustainable geo eco tourism development that aligns with local wisdom and community values